Manajemen Strategi Pemerintah Desa dalam Pengembangan Bumdes Cemerlang di Desa Baturaden Kecamatan Batujaya Kabupaten Karawang - Nunik Syauqina; Dadan Kurniansyah; Gun Gun Gumilar (Jurnal Ilmiah Wahana Pendidikan, 2022)
The main point of the progress of a country depends on the village, it is impossible for a country to be said to be a developed country if the regions in the country are lagging behind. Therefore, massive and sustainable village development is carried out in order to achieve the progress of a country which must be carried out from the lowest level, namely the village. The establishment of Village Owned Enterprises (BumDes) is one of the village government's efforts in carrying out village development. In 2020, BumDes Cemerlang was selected as one of the best BumDes in Karawang Regency. The purpose of this study is because the author wants to know how the Strategic Management carried out by the Baturaden Village Government in developing the Cemerlang BumDes as one of the Village Government's efforts in increasing economic growth and welfare of rural communities. In this study, the authors used qualitative research methods with a descriptive approach. The strategic management carried out by the Baturaden Village Government in developing the BumDes Cemerlang includes the first process, namely observing the environment by looking at opportunities based on community needs. The second process is strategy formulation, carried out by means of product development, pricing, and financial strategy. The third process is the implementation of the strategy, where in 2021, Bumdes Cemerlang has succeeded in developing the programs they carry out. The fourth process, namely evaluation or control, in supervising the activities and all programs of Bumdes Cemerlang, the party authorized to supervise it is the Village Head and BPD which is carried out once a year, and also every time a new program will be held. The strategic management carried out by the Baturaden Village Government in developing the Brilliant BumDes is by observing the environment, formulating strategies, implementing strategies, and evaluating or controlling.